1979
DOI: 10.3109/00016347909157792
|View full text |Cite
|
Sign up to set email alerts
|

Dysmenorrhea During Adolescence

Abstract: Different aspects of the menstrual pattcrn including dysmenorrhea, premenstrual tension and working performance during menstruation was studied in three different investigations.The first study includes 5458 adolescent girls aged 10 to 20. The incidence of invariably painful menstruation was 7.2 per cent during the first gynecological year and 26 per cent five years later. A correlation was found between mothers and daughters for dysmenorrhea as well as for premenstrual tension.In a second study including 331 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(18 citation statements)
references
References 12 publications
(3 reference statements)
3
15
0
Order By: Relevance
“…In approximately 10% of these dysmenorrheic subjects, the symptoms are disabling enough to cause incapacitation for one to two days a month (1)(2)(3)(4). Primary dysmenorrhea is the most common gynecologic complaint.…”
Section: Introductionmentioning
confidence: 99%
“…In approximately 10% of these dysmenorrheic subjects, the symptoms are disabling enough to cause incapacitation for one to two days a month (1)(2)(3)(4). Primary dysmenorrhea is the most common gynecologic complaint.…”
Section: Introductionmentioning
confidence: 99%
“…Interdisciplinary research represented in the biopsychosocial model also has been recommended as a tool to investigate premenstrual syndrome (Abplanalp, 1980;Dennerstein, SpencerGardner, & Burrows, 1981;Clare, 1985;Txunnell, 1986;Wilson, 1990), a combination of timedelineated physical emotional and behavioral symptoms that occur before menstruation but after ovulation (luted phase), and regress or disappear during menstruation, not solely the result of environmental stress, the occur-JOURNAL OF HEALTH EDUCATION-NOVEMBEWDECEMBER 1992 (Delaney, Lupton, & Toth, 1976); societal milieuconveyscornplex negative meanings (McKeever, tially responsible for menstrual symptomatology (Aubuchont Calhoun, 1985) and premenstrual tension (Widholm, 1979). Because of this, it has been suggested that a woman has more than a biological clock to signal discomfort (Paige, 1973).…”
Section: Carola Wilson Isan Assistant Professor In the Skhool Ofhealmentioning
confidence: 96%
“…Cer tain stud ies (Widholm, 1979;van den Akker et al, 1987) suggest that women whose mothe r s re por ted premenstrual tension were more likely (70% of daughters of affected mothers vs. 37% of daughters of unaffected mothers) to develop premenstrual mood symptoms. Also, concordance rates for symptoms of PMS are significantly higher in monozygotic twins (93%) compared to dizygotic twins (44%) or sibling controls (31%) (Dalton et al, 1987).…”
Section: Familial Factorsmentioning
confidence: 99%